Context sensitive solution (CSS) in designing urban thoroughfare [electronic resource] - Lim, Zhi Min, 1990-; Chau Loon Wai, supervisor (2015)
Project Paper (Sarjana Muda Perancangan Bandar dan Wilayah) - Universiti Teknologi Malaysia, 2015